1999
DOI: 10.1016/s0735-1097(99)00270-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biphasic and conventional monophasic defibrillation on postresuscitation myocardial function

Abstract: Lower-energy biphasic waveform shocks were as effective as conventional higher energy monophasic waveform shocks for restoration of spontaneous circulation after 4 and 7 min of untreated VF. Significantly better postresuscitation myocardial function was observed after biphasic waveform defibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(91 citation statements)
references
References 31 publications
3
80
0
3
Order By: Relevance
“…In confirmation of earlier investigations, postresuscitation myocardial dysfunction was largely reversed after 72 hours in the absence of interruption other than for Ͻ3 seconds during delivery of the shock. 2, 29 We therefore implicate interruptions in chest compression, resulting in critical reductions in myocardial perfusion and with exacerbation of global ischemic injury of the heart, as explanations for the outcomes, especially in settings in which ventricular fibrillation consumes disproportionately large myocardial oxygen demands. 30,31 To this extent, the present studies only extend the well-established understanding that the longer the duration of myocardial ischemia, the greater is the impairment in myocardial function, whether it be a result of regional or global ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In confirmation of earlier investigations, postresuscitation myocardial dysfunction was largely reversed after 72 hours in the absence of interruption other than for Ͻ3 seconds during delivery of the shock. 2, 29 We therefore implicate interruptions in chest compression, resulting in critical reductions in myocardial perfusion and with exacerbation of global ischemic injury of the heart, as explanations for the outcomes, especially in settings in which ventricular fibrillation consumes disproportionately large myocardial oxygen demands. 30,31 To this extent, the present studies only extend the well-established understanding that the longer the duration of myocardial ischemia, the greater is the impairment in myocardial function, whether it be a result of regional or global ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] One study found that the use of biphasic waveforms was associated with significantly better postresuscitation myocardial function than monophasic waveforms, even with the same high energies and capacitance typically used for monophasic defibrillation. 36 These studies demonstrate the safety of pediatric defibrillation shocks, even at energy doses significantly higher than the current 4-J/kg recommendations, and especially when the number of shocks delivered is minimized.…”
Section: Aed Energy and Waveform Safety And Efficacymentioning
confidence: 70%
“…9) The cause of increased risk may be postulated that the negative inotropic consequences of the shock itself could increase the risk of death, especially when the patient receives multiple shocks due to oversensing or in response to ongoing supraventricular tachycardia. [10][11][12][13] Thus, effective strategies to reduce ICD shocks are desirable. Antiarrhythmic medication is frequently administered in patients with an ICD.…”
Section: Discussionmentioning
confidence: 99%